2021
DOI: 10.1002/suco.202100286
|View full text |Cite
|
Sign up to set email alerts
|

Compressive strength of efficient self‐compacting concrete with rice husk ash, fly ash, and calcium carbide waste additives using multiple artificial intelligence methods

Abstract: The principal benefit of mixed concrete is to minimize the disadvantages of certain complementary cement ingredients by combining them with other better materials so that overall costs are managed and efficiencies of concrete production are increased. The structural and economic characteristics of concrete can also be improved. In this work, the compressive strength (CS) of selfcompacting concrete (SCC) was assessed and their interrelations were addressed using binary and ternary cementitious combinations of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 126 publications
(187 reference statements)
0
7
0
Order By: Relevance
“…The use of artificial intelligence in the field of civil engineering 33–44 today more than ever is being considered 45 . The application of artificial intelligence considerably reduces the cost and time of experimental studies, provided that there is sufficient laboratory data in this area 46 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of artificial intelligence in the field of civil engineering 33–44 today more than ever is being considered 45 . The application of artificial intelligence considerably reduces the cost and time of experimental studies, provided that there is sufficient laboratory data in this area 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies showed that in addition to the concentration of chloride ions, increasing the temperature also significantly reduces the chloride ions penetration resistance. [30][31][32] The use of artificial intelligence in the field of civil engineering [33][34][35][36][37][38][39][40][41][42][43][44] today more than ever is being considered. 45 The application of artificial intelligence considerably reduces the cost and time of experimental studies, provided that there is sufficient laboratory data in this area.…”
Section: Introductionmentioning
confidence: 99%
“…81 Autogenous shrinkage versus ln(RH) for concrete with various quantities of IC water is exhibited in Figure 11. The linear correlation between the autogenous shrinkage of concrete and ln RH ð Þ could be described as Equation (19):…”
Section: Relationship Between Autogenous Shrinkage and Irhmentioning
confidence: 99%
“…Proper curing plays a vital role in ensuring the intended performance and durability of concrete 19,20 . Traditional external curing was not effective enough because merely the concrete surface can be cured due to the poor permeability 21,22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation